2023
DOI: 10.2174/1567201819666220627100857
|View full text |Cite
|
Sign up to set email alerts
|

Overcome of Cisplatin Resistance in Ovarian Cancer by Combination of Low-intensity Ultrasound and Cisplatin

Abstract: Backgorund: Platinum-based chemo therapeutics are main treatment option for the treatment of ovarium cancer. However, development of drug resistance is one of the major issues in chemotherapy. Even targeting a specific pathway may not produce an efficient sensitization to the chemo agent due to various pathways in related to developing resistance against cisplatin. Hence, more effective strategies against drug resistance are essential for the cancer treatment. In the presence of the ultrasonic waves, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…High-frequency keywords and burst words help scholars clarify future research directions in related fields. After keyword network and burst word analysis, we found that LIPUS-related research has gradually progressed from previous growth factors (36,37), fracture healing (38)(39)(40)(41), and integrins (42)(43)(44) to fields such as oxidative stress (45), regeneration (46,47), and tumors (48)(49)(50). This suggests that the exploration of molecular biological mechanisms for LIPUS is gradually deepening, and its application areas are gradually expanding to major diseases such as cancer, proving once again the broad application prospects and clinical value of LIPUS.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency keywords and burst words help scholars clarify future research directions in related fields. After keyword network and burst word analysis, we found that LIPUS-related research has gradually progressed from previous growth factors (36,37), fracture healing (38)(39)(40)(41), and integrins (42)(43)(44) to fields such as oxidative stress (45), regeneration (46,47), and tumors (48)(49)(50). This suggests that the exploration of molecular biological mechanisms for LIPUS is gradually deepening, and its application areas are gradually expanding to major diseases such as cancer, proving once again the broad application prospects and clinical value of LIPUS.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cancer chemotherapy has limitations such as drug resistance and drug side effects. The effectiveness of LIPUS combined with platinum to overcome chemoresistance has been demonstrated in platinum-resistant ovarian cancer cells by measuring cell viability, colony formation, and cell cycle analysis ( 55 ). The principle may be that LIPUS improves cell membrane permeability and intracellular drug concentration increases the therapeutic effect.…”
Section: Lipus Improves the Efficacy Of Cancer Chemotherapy And Radio...mentioning
confidence: 99%